2002
DOI: 10.1002/chin.200211081
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Liquid Crystals with Multiple Fluorinated Bridges in the Mesogenic Core Structure

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…(1) The Etherification Method Ekkehard [1] have reported that the difluoromethyl benzene derivatives were prepared with benzaldehyde derivatives and SF 4 .…”
Section: The Ways Of the Directed Fluorinationmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) The Etherification Method Ekkehard [1] have reported that the difluoromethyl benzene derivatives were prepared with benzaldehyde derivatives and SF 4 .…”
Section: The Ways Of the Directed Fluorinationmentioning
confidence: 99%
“…The synthetic route of the compound which includes -CF 2 O-(2) The carbonylation method Guillaume Magueur [4] has reported that the replacement of the carbonyl function by a difluoroethylene moiety can resulted in a better antimalarial activity. At that stage, the selective reaction can access to the target compound.…”
Section: Sf4mentioning
confidence: 99%